Fresno's Martin Luther King, Jr. March from City Hall to Saroyan Theatre - Watkins, Howard::::::::: (1987)
Program emcees Reverend Betty Pingel and ? At Saroyan Theatre lectern covered with Martin Luther King, Jr. photograph